LAUGH NOT TO SUFFER: THE CORONAVIRUS PANDEMIC THROUGH THE HUMOR OF MEMES ON WHATSAPP - Balarezo-López, Gunther (2020)
One of the most practical and fastest ways to spread messages with humorous content is through the cell phone with the WhatsApp application. Among the most common messages sent are memes, a sarcastic and ironic form of humor from reality. These messages have gone viral during the coronavirus pandemic as a way to face adversity with humor. In this sense, this work aims to describe the memes about the coronavirus that were spread through the cell phone during the days of social confi nement in Peru from March 16th to June 30th, 2020. It was found that people's creative capacity has no limits to express their opinions on the problems that arise. It can be concluded that in the face of the adversity of this disease, one of the ways to deal with it is through humor, to make the problems that arose on a day-to-day basis more bearable. Keywords: coronavirus - COVID-19 - humor -  memes - WhatsApp